Higher education: free tuition vs. quotas vs. targeted vouchers - Andrade,Eduardo de Carvalho (2010)
This paper compares theoretically three alternative university systems: the current one adopted in Brazil, in which students who perform better in the entering exam obtain the right to attend the public university without paying the full tuition; a system of affirmative action quotas in public universities, to benefit low income students; and a targeted vouchers system that can be used either to pay private or public university tuiton. The comparison indicates that the last system leads to: (i) a higher quality of the labor force; (ii) a more efficient allocation of resources; and (iii) a greater social mobility.